The Effect of Entrepreneurship Education and Self-Efficacy on Students' Entrepreneurial Attitude and Entrepreneurial Intention - Ferdianto, Martinus Gilbert; Annas, Mohammad; Tannady, Hendy (Journal of Social Science and Business Studies, 2025)
Entrepreneurship is an important factor in economic development and economic progress in a country. Students become one of the role holders in making the entrepreneurship. By studying the factors that influence students' attitudes and willingness to innovate and express themselves, they can improve their performance for entrepreneurship. From the perspective of planned behavior theory, it can analyze the influence of entrepreneurship education on students and student self-efficacy on students' attitudes and interests in entrepreneurship. This study used a sample of 166 students in DKI Jakarta by distributing questionnaires in the form of a Google form, which later the data obtained would be tested for hypotheses and the results obtained. First, entrepreneurship education for students has a significant positive effect on entrepreneurial intentions, but has no effect on students' entrepreneurial attitudes. Student self-efficacy has a significant positive effect on entrepreneurial attitudes and entrepreneurial intentions of students.